(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The Indian Constitution’s Directive Principles of State Policy are outlined in Part IV. However these standards are rules and are not enforceable in that frame of mind of regulation anyway they are crucial in the administration of the country. Article 44 of the Constitution, which mandates the state to enact a uniform civil code, provides one such directive principle. Different headings have been given by the Zenith Court for its execution notwithstanding, because of exorbitant politicization in our country it is as yet a far off dream. Personal matters like marriage, divorce, and adoption are not governed by a single body of law. Different individual regulations are relevant to various strict networks who dwell in our country. These regulations find their source and authority in their strict texts and customs which accommodates orientation prejudicial practices in all structures and frequently is one-sided towards guys than that of females. This paper targets accomplishing a harmony between Right to Opportunity of Religion and Right to Correspondence by isolating the ’fundamental strict practices’ and ’mainstream exercises’. In this manner one can say that the need of great importance is to sanction a Uniform Common Code however that should be done gradually and continuously in the wake of making individuals particularly the minorities, mindful about its degree and degree as well as their freedoms.